Case reportRhabdomyolysis following severe hypokalemia caused by Conn’s syndrome - Gonerska-Szadkowska, Anna; Wittych-Długosz, Joanna; Rzymski, Paweł; Makarewicz, Jacek; Szmidt, Mirosław; Lewiński, Andrzej (Archives of Medical Science, 2007)
Rhabdomyolysis denotes a clinical and laboratory syndrome that results from a rapid breakdown of skeletal muscle cells. This releases potentially toxic muscle cell components into the circulation which may cause life-threatening complications including myoglobinuric acute renal failure, cardiac arrest or disseminated intravascular coagulation. During rhabdomyolysis the injured muscle leaks potassium leading to hyperkalemia. In primary aldosteronism, mineralocorticoid activity leads to hypokalemia which can be severe enough to cause rhabdomyolysis. We report an unusual case of rhabdomyolysis with hypokalemia due to Conn’s syndrome.